A novel benzoxazine/cyanate ester blend with sea-island phase structures1. Issue 29 (7th August 2015) - Li, Xiaodan; Luo, Xiaoyong; Gu, Yi
<x xml:space="preserve">Abstract</x> A novel C-BOZ/BADCy blend with sea-island phase structures was successfully prepared via reaction-induced phase separation.